The Stock Market's Anticipation of the Trump 2024 Election: The Case of Sustainable Business Models - Dennis Koch; Dirk Schiereck (Business Strategy and the Environment, 2025)
This study examines the impact of green revenues on US stock price reactions around Donald Trump's 2024 election win. Firms' green revenue share (GRS) is significantly associated with negative cumulative abnormal returns (CARs) post-election, exhibiting a nonlinear effect that intensifies at higher GRS levels. However, stock markets showed no anticipating revaluation of green business models during the weeks before the election. Instead, investors reacted sharply to two unanticipated key pre-election events, the Trump assassination attempt and Harris' candidacy announcement, highlighting sensitivity to anticipated shifts in green policy. Remarkably, the revaluation of green business models did not take place uniformly across the entire country. The state political environment moderates this effect, as green firms in Democratic states experienced more negative CARs than those in Republican states.
Keywords: 650; ESG; event study; green revenues; stock price reactions; sustainability; Trump; US election